ANALISIS MINAT BELAJAR SISWA PEREMPUAN TINGKAT ATAS PADA MATA PELAJARAN PENDIDIKAN JASMANI DI SEKOLAH DASAR - Septian Doly Sitinjak; Deni Ardian Sitompul; Ivan Gunawan Purba; Samuel Siahaan; Nurkadri Nurkadri (Universitas Negeri Medan, 2024)
Analysis of upper level female students’ learning interest in physical education in primary scool. Physical education is a subject that requires physical activity. Physical activity becomes a benchmark in determining students’ interest in learning. Learning interest is influenced by internal factros and external factors of upper grade famale students which include 4th, 5th, and 6th, grade famale students, descriptive and inferential analysis will be crried out. This research is a qualitative research instuments in the form of questionnaires and interview results. The results of this study indicate that 76% of famale students at SD Negeri 068474 medan are categorized as strong. This means that as many as 76% of the total sample have an interest in praticipating in sthe physical education learning process.